Culturally Informed, Codesigned, Supportive Care for Aboriginal and Torres Strait Islander People With Cancer and Their Families. Issue 2 (3rd April 2022) - Lethborg, Carrie; Halatanu, Fay; Mason, Toni; Posenelli, Sonia; Cleak, Helen; Braddy, Lisa
ABSTRACT: Aboriginal and Torres Strait Islander people experience significant disparities in accessing cancer care and in cancer outcomes when compared with non-Indigenous Australians. Social workers and Aboriginal Hospital Liaison Officers from an inner-city hospital partnered with local Aboriginal organisations to develop, implement, and evaluate a culturally informed model of supportive cancer care. The initiative adopted an "appreciative inquiry" approach and engagement with Indigenous stakeholders, drawing on the Aboriginal and Torres Strait Islander Quality Improvement Framework and Toolkit for Hospital Staff (AQIFTHS, 2015). Using a process of codesign, strategies were developed with consumers to address the social and cultural determinants of health across the cancer journey. The new evidence-based model of care incorporated culturally informed identification of needs, culturally appropriate engagement, and maintenance of respectful connections to develop codesigned care plans with tailored information and provide practical support and advocacy. Findings illustrate the complex challenges faced by Aboriginal and Torres Strait Islander people living with cancer as well as their strengths. AQIFTHS processes and model of care provide guidance for social workers and other health professionals seeking to partner with stakeholders to promote health equity and improve supportive cancer care in accordance with optimal care guidelines and national quality standards. IMPLICATIONS Supportive care needs of Aboriginal and Torres Strait Islander people living with cancer are often complex and multifaceted, but links with community and culture are noted strengths. Social workers in Australian health settings have an important role in improving access and promoting a culturally responsive model of care for this population. Appropriate support can only occur when it is codesigned with the individual patient and their family members, Aboriginal Hospital Liaison Officers, and community.